2017
DOI: 10.5296/ijafr.v7i2.12118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corporate Governance Practices on Firm's Cash Holdings in an Emerging Market: A Panel Data Analysis

Abstract: The aim of the study was to examine the impact of corporate governance practices on firm's cash holdings of listed manufacturing companies in Sri Lanka, using panel data extracted from the financial statements of the companies listed on Colombo Stock Exchange. Corporate governance practices of Sri Lankan listed manufacturing companies were measured by board independence, board size, CEO duality, audit committee meetings and audit committee members, cash holdings were measured by percentage of cash and cash equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 11 publications
1
6
2
8
Order By: Relevance
“…Kengatharan [26] by taking 26 manufacturing companies listed on the Colombo Stock Exchange from the period of 2011-2015. The findings showed that CEO-duality and leverage has significant negative impact whereas firm size and audit committee meetings firm size had positive impact while Board independence, board size and audit committee members has an insignificant impact on cash holdings…”
Section: F Corporate Cash Holdings and Corporate Governance Around Th...mentioning
confidence: 99%
“…Kengatharan [26] by taking 26 manufacturing companies listed on the Colombo Stock Exchange from the period of 2011-2015. The findings showed that CEO-duality and leverage has significant negative impact whereas firm size and audit committee meetings firm size had positive impact while Board independence, board size and audit committee members has an insignificant impact on cash holdings…”
Section: F Corporate Cash Holdings and Corporate Governance Around Th...mentioning
confidence: 99%
“…In the literal sense of word, the overwhelming majority of prior studies are devoted to examine the direct nexus between CG and firm's cash holdings. Thereby, it is worth to study what was predominantly neglected by the previous researchers (see Cruz, 2015; Hassanein and Kokel, 2019; Kengatharan, 2017; Roy, 2018). Second , in the context of the contradictory and mixed findings in prior research, it is logically and rationally to revisit the above-mentioned relationship by including a moderator variable.…”
Section: Introductionmentioning
confidence: 99%
“…This result shows that 88.100 per cent of cash holdings can be explained by all independent and control variables; 11.900 per cent was explained by other variables not tested in this study. 2017Ayed, 2022Gul et al, 2020;Kengatharan, 2017) who found that the proportion of independent board of directors was not a factor that had a significant influence on determining the number of cash holdings.…”
Section: Resultsmentioning
confidence: 99%
“…An audit committee that actively holds meetings could positively impact the excess cash or cash reserves (Choi et al, 2020). Conversely, (Kengatharan, 2017) in his research found that meetings held by the audit committee did not affect the determination of the amount of cash holdings.…”
Section: Theoretical Reviewmentioning
confidence: 92%